The sustainability of participatory local governance in Barangay Quinangyana, Bingawan, Iloilo. - Londres, Louie Marie Secaluya
This study primarily aimed to determine the sustainability of Participatory Local Governance (PLG) in Barangay Quinangyana through the Ipahayag sa Barangay. Specifically, the research sought to address the following objectives: (1) to describe the Ipahayag sa Barangay as a PLG mechanism in Barangay Quinangyana; (2) to determine the influences of the Ipahayag sa Barangay on the responsiveness of the barangay LGU; (3) to determine the influences of the Ipahayag sa Barangay on the people's participation in governance and in service delivery; and (4) to predict the sustainability of LPG in Barangay Quinangyana through the Ipahayag sa Barangay. These objectives were addressed through the use of survey method and focused group discussion. Secondary data were also obtained to supplement the information needed., Results showed that Ipahayag sa Barangay indeed, has an impact on the people's participation and government 's responsiveness in service delivery. As for the participation of the people, the respondents were basically aware and interested of the services and they also utilize the said services. In particular, peace and order and water services received the highest response of awareness; agricultural services generated the highest responses for attitude; and the highest responses for utilization were received by the service regarding peace and order. Meanwhile, the barangay LGU was assessed by the respondents to be responsive as indicated by the high responses which reveal that the barangay government is prompt, effective and satisfactory in delivering basic social services. However, the barangay was held to be the most responsive on peace and order service which received the highest response rate with regards promptness, effectiveness and satisfaction of the constituents in service library. From these findings, it was concluded that PLG in Barangay Quinangyana is sustainable through the Ipahayag sa Barangay. However, some factors were identified which could also hamper the further sustainability of PLG in the above mentioned barngay. For the purpose of future studies regarding Participatory Local Governance, the researchers recommend that they: (1) should focus on the aspects of PLG such as planning decision-making, policy implementation and policy monitoring; (2) should cover a broader sample size which enable the researchers to infer data and generalize these as true for the entire population of the locale of the study; and (3) should also look into the association or correlative aspect of people's participation and government's responsiveness in pursuit of participatory locale governance. with regrad developing new policies related to PLG, the researchers recommend the following: (1) mechanisms on effective mobilization of the constituents to be involved in PLG programs such as the Ipahayag sa Barangay should be institutionalized; (2) information dissemination regarding PLG and its working should be improved through a series of seminars, lectures, and fora; and, (3) efforts to tap the private sector to get involved in PLG endeavors in order to further strengthen the sustainability of participation in local governance.